2016
DOI: 10.1089/bio.2015.0069
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Oocytes Derived from Vitrified Ovarian Follicles Cultured in Two- and Three-Dimensional Culture System in the Presence and Absence of Kit Ligand

Abstract: The aim of this study was to evaluate the effects of Kit Ligand (KL) on the growth of vitrified follicle, oocyte quality, and embryo development in two- and three-dimensional culture systems. Vitrified and nonvitrified mouse whole ovaries were cultured for 1 week, then their isolated preantral follicles were cultured for 12 days in two- or three-dimensional culture systems in the presence and absence of KL. The growth and diameter of follicles, maturation of oocytes, and hormonal level were assessed. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Abdi et al . also demonstrated that the mouse ovarian vitrification had no harmful effects on the steroidogenesis, growth and maturation of isolated follicles after two‐step in vitro culture of ovarian tissue . In the other point of view, the fertilization rate of MII oocytes derived from vitrified ovaries was significantly lower as compared with MII oocytes derived from the in vivo group.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Abdi et al . also demonstrated that the mouse ovarian vitrification had no harmful effects on the steroidogenesis, growth and maturation of isolated follicles after two‐step in vitro culture of ovarian tissue . In the other point of view, the fertilization rate of MII oocytes derived from vitrified ovaries was significantly lower as compared with MII oocytes derived from the in vivo group.…”
Section: Discussionmentioning
confidence: 62%
“…The isolated preantral follicles ( n > 150 in each group) from cultured ovaries were encapsulated in sodium alginate as described previously . Encapsulated follicles were cultured in α‐MEM medium supplemented with 5% FBS, 100 mIU/mL rFSH or Gonal‐f (Serono), 1% ITS (Gibco), 100 mg/mL penicillin and 50 ng/mL streptomycin under mineral oil at 37°C with 5% CO 2 for 12 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, every other day, half of the medium was replaced by fresh medium. [ 22 ] At the end of culture period, analysis of developmental genes ( PCNA and FSHR ) and steroid hormones (17-β estradiol, progesterone, and dehydroepiandrosterone (DHEA)) was performed and also the released metaphase II (MII) oocytes in three groups of culture were collected and randomly considered for reactive oxygen species (ROS) assay.…”
Section: Ethodsmentioning
confidence: 99%
“…The preantral follicle was encapsulated in sodium alginate. [ 22 ] Briefly, alginate was dissolved in deionized water at a concentration of 1% (w/v) and was then mixed with activated charcoal (0.5 g of charcoal per gram of sodium alginate). Following charcoal treatment, the prepared sodium alginate solution was sterile filtered through 0.22-μM filters.…”
Section: Ethodsmentioning
confidence: 99%